High‐Performance Wide Bandgap Copolymers Using an EDOT Modified Benzodithiophene Donor Block with 10.11% Efficiency. Issue 6 (10th October 2017) - Feng, Kui; Yang, Guofang; Xu, Xiaopeng; Zhang, Guangjun; Yan, He; Awartani, Omar; Ye, Long; Ade, Harald; Li, Ying; Peng, Qiang
Abstract: Newly developed benzo[1, 2‐b:4, 5‐b′]dithiophene (BDT) block with 3, 4‐ethylenedioxythiophene (EDOT) side chains is first employed to build efficient photovoltaic copolymers. The resulting copolymers, PBDTEDOT‐BT and PBDTEDOTFBT, have a large bandgap more than 1.80 eV, which is attributed to the increased steric hindrance between the BDT and EDOT skeletons. Both copolymers possess the satisfied absorptions, low‐lying highest occupied molecular orbital (HOMO) levels and high crystallinity. Using the fluorination strategy, PBDTEDOT‐FBT exhibits a wider and stronger absorption and a deeper HOMO level than those of PBDTEDOT‐BT. PBDTEDOT‐FBT:[6, 6]‐Phenyl C71 butyric acid methyl ester (PC71 BM) blend also shows the higher hole mobility and better surface morphology compared with the PBDTEDOTBT:PC71 BM blend. Combination of above advantages, PBDTEDOT‐FBT devices exhibit much higher power conversion efficiency (PCE) of 10.11%, with an improved open circuit voltage (Voc ) of 0.86 V, short circuit current densities (Jsc ) of 16.01 mA cm −2, and fill factor (FF) of 72.6%. This work not only provides a newly efficient candidate of BDT donor block modified with EDOT conjugated side chains, but also achieves high‐performance large bandgap copolymers for polymer solar cells (PSCs) via the synergistic effect of fluorination and side chain engineering strategies. Abstract : Combination of fluorination and side chain engineering strategies, newly developed benzo[1, 2‐b:4, 5‐b′]dithiophene block with 3, 4‐ethylenedioxythiophene side chains is first employed to build the efficient large bandgap copolymers with efficiency of 10.11%.